Unmet information needs of men with breast cancer and health professionals - Bootsma, Tom I. (Psychooncology, 2020)
OBJECTIVE: Male breast cancer (MBC) is rare. Information about breast cancer is usually designed for female patients. However, in males this disease and some side effects differ from its female counterpart. Therefore, there is a need for male‐specific information. The aim was to assess unmet information needs of (a) MBC patients and (b) health professionals. METHODS: Dutch MBC patients (diagnosed between 2011 and 2016 in 21 hospitals), patient advocates and partners were invited to participate in focus groups and/or complete a paper‐based questionnaire on information needs. In addition, an online questionnaire on information needs was sent to health professionals involved in MBC patient care. RESULTS: In three focus groups with MBC patients (N = 12) and partners (N = 2) the following unmet information themes were identified: patients' experiences/photographs, symptoms, (delay of) diagnosis, treatments, side effects, follow‐up, psychological impact/coping, genetics and family, research and raising awareness. 77 of 107 MBC patients (72%) completed the questionnaire: most patients lacked information about acute (65%) or late (56%) side effects, particularly sexual side effects. Among health professionals, 110 of 139 (79%) had searched for MBC‐related information, specifically: patient information, anti‐hormonal therapy, genetic testing, research, and psychosocial issues. CONCLUSIONS: Unmet information needs in MBC patients and health professionals were identified. Specific information on MBC should be developed to improve timely diagnosis, quality of life, treatment, and survival. A targeted website is an ideal tool to meet these needs. Therefore, we integrated these results into a user‐centered design to develop an informative website, www.mannenmetborstkanker.nl.